On-chip label-free plasmonic based imaging microscopy for microfluidics. (13th August 2018) - Arora, P; Krishnan, A
Abstract: In this work, we demonstrated an on-chip label-free imaging microscopy using real and Fourier Plane (FP) dark field images of surface plasmons, by integrating engineered plasmonic substrates with different shapes of microfluidic channels. After successful integration of fabricated plasmonic nanostructures with SU-8 based microfluidic channels, on-chip label-free index monitoring of analytes with different refractive indices was demonstrated and an index resolution of 1.63 × 10 −4 RIU was achieved by quantifying CMYK components of captured images. Label-free imaging for interface of colorless miscible and immiscible analytes flowing on plasmonic nanostructures in the microfluidic channels was performed using color-selective filtering nature of plasmonic nanostructures. Hydrodynamic focusing where the width of the focused stream of one liquid was controlled by the relative flow rates of the three liquids was demonstrated and utilized to capture the flow of air bubbles on plasmonic nanostructures with real and FP images. Since, the imaging is realized on a chip and does not need any complicated and bulky arrangement, it will benefit the development of flat optical components for sensing applications and will be well suited for on-chip point of care diagnostics.